2009
DOI: 10.1007/s12237-009-9217-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Benthic Nutrient Flux During Monsoon Periods in a Coastal Lake Formed by Tideland Reclamation

Abstract: Sediment and water quality were investigated in an artificial coastal lake (Saemangeum Lake, Korea) that was formed by constructing a 33-km long sea-dyke offshore from the mouths of two adjacent rivers, which discharge into the Yellow Sea. Sediment showed drastic increases in fine fraction (silt and clay) after the dyke construction. TN, TP, and OC contents in the sediment showed the similar spatial variation to that of fine fraction. A mixing model indicated benthic fluxes of nutrients such as PO 4 , NH 4 , a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…After the construction of the dike, the mixing of seawater and lake water decreased and the in uence of freshwater from the upstream watershed expanded, resulting in a sharp increase in the concentrations of chlorophyll-a and nutrients in the lake (Jeong and Yang 2015). It was also found that an excess of nutrients was supplied from the bottom water of the lake (Kim et al 2009;Jeong et al 2014). In literature data from seawall completion (2006) to 2010, hypoxia with strong salinity strati cation was observed only in the mid-upstream region of the lake, which is directly affected by river in ow (Jeong and Yang 2015).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…After the construction of the dike, the mixing of seawater and lake water decreased and the in uence of freshwater from the upstream watershed expanded, resulting in a sharp increase in the concentrations of chlorophyll-a and nutrients in the lake (Jeong and Yang 2015). It was also found that an excess of nutrients was supplied from the bottom water of the lake (Kim et al 2009;Jeong et al 2014). In literature data from seawall completion (2006) to 2010, hypoxia with strong salinity strati cation was observed only in the mid-upstream region of the lake, which is directly affected by river in ow (Jeong and Yang 2015).…”
Section: Study Areamentioning
confidence: 99%
“…The depth of the lake increased gradually from upstream to midstream and deepened sharply downstream; the maximum water depth was ~ 40 m near the Sinshi sluice gate (Shin et al 2012). The average annual in ow of rivers owing from the upstream watershed of the lake is 1,100 × 10 6 m 3 /year from the Mangyeong River and 700 × 10 6 m 3 /year from the Dongjin River (Kim et al 2009), and precipitation in the watershed is concentrated from June to September. Accordingly, the strati cation of the lake is strengthened during periods of high river in ow (Jeong and Kwak 2020).…”
Section: Study Areamentioning
confidence: 99%
“…In the case of Korea, the Korean plain accounts for less than 30–40% of the total area, most of which is covered with forests, and the proportion of land fit to cultivate agricultural products is low [ 10 ]. Therefore, the tidal mudflats in the West Sea were reclaimed to create arable land [ 11 ]; these areas were converted and utilized for various purposes such as industrial and urban development, power plants, and agriculture through the conversion of coastal wetlands with techniques such as reclamation and levees [ 12 ]. After the tidal mudflats are reclaimed, the soil salinity and vegetation in the area change rapidly, so land use planning is important because the soil in the reclaimed area is characterized by highly salinity [ 13 ].…”
Section: Introductionmentioning
confidence: 99%